Immunoexpression profile of hypoxia-inducible factor (HIF) targets in potentially malignant and malignant oral lesions: a pilot study - Gholami, Shakiba; Chamorro-Petronacci, Cintia; Pérez-Sayáns, Mario; Suárez Peñaranda, José; Longatto-Filho, Adhemar [UNESP]; Baltazar, Fátima; Afonso, Julieta (FapUNIFESP (SciELO), 2023)
Oral potentially malignant disorders (OPMD) are associated with an increased risk of oral squamous cell carcinoma (OSCC). OSCC has an aggressive profile and is the most prevalent among different head and neck malignancies. Most OSCC patients are diagnosed with advanced stage tumors and have a poor prognosis. Cancer cells are able to reprogram their metabolism, even in the presence of oxygen, enhancing the conversion of glucose to lactate via the glycolytic pathway, a phenomenon mainly regulated by hypoxia-inducible factor (HIF) signaling. Thus, several glycometabolism-related biomarkers are upregulated. This study aimed to evaluate the immunoexpression of the HIF targets GLUT1, GLUT3, HK2, PFKL, PKM2, pPDH, LDHA, MCT4, and CAIX in OPMD and OSCC samples, in order to identify potential correlations between biomarkers' immunoexpression, clinicopathological features, and prognostic parameters. OSCC and OPMD samples from 21 and 34 patients (respectively) were retrospectively collected and stained for the different biomarkers by immunohistochemistry. CAIX and MCT4 expressions were significantly higher in OSCC samples when compared with OPMD samples, while the rest were also expressed by OPMD. GLUT3 and PKM2 alone, and the concomitant expression of more than four glycometabolism-related biomarkers were significantly correlated with the presence of dysplasia in OPMD. When considering OSCC cases, a trend toward increased expression of biomarkers and poor clinicopathological features was observed, and the differences regarding HK2, PFKL, LDHA and MCT4 expression were significant. Moreover, HK2 and CAIX were correlated with low survival rates. GLUT1 and GLUT3 were significantly associated with poor outcome when their expression was observed in the hypoxic region of malignant lesions. OPMD and OSCC cells overexpress glycolysis-related proteins, which is associated with aggressive features and poor patient outcome. Further research is needed to deeply understand the glycolic phenotype in the process of oral carcinogenesis.